2016
DOI: 10.1038/ncomms10323
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of active processes modulates tension and drives phase transition in self-renewing, motor-driven cytoskeletal networks

Abstract: The actin cytoskeleton—a complex, nonequilibrium network consisting of filaments, actin-crosslinking proteins (ACPs) and motors—confers cell structure and functionality, from migration to morphogenesis. While the core components are recognized, much less is understood about the behaviour of the integrated, disordered and internally active system with interdependent mechano-chemical component properties. Here we use a Brownian dynamics model that incorporates key and realistic features—specifically actin turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 66 publications
(97 reference statements)
12
103
0
Order By: Relevance
“…We employed our previous coarse-grained Brownian dynamics model for actomyosin structures [13]. In the model, actin filaments, actin cross-linking proteins (ACPs), and motors are simplified into interconnected cylindrical segments (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We employed our previous coarse-grained Brownian dynamics model for actomyosin structures [13]. In the model, actin filaments, actin cross-linking proteins (ACPs), and motors are simplified into interconnected cylindrical segments (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we demonstrated that actin turnover modulates the buildup and sustainability of tension generated by actomyosin networks [13]. We tested effects of actin turnover on bundle formation and tension generation by imposing actin treadmilling at various rates ( k t,A ) under a condition where bundles generate unsustainable tension and eventually form aggregates in the absence of any turnover ( R M = 0.08 and R ACP = 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulating macromolecule stability and interactions in a eukaryotic-like cell requires a large effort for the presence of localized and pervasive structures (Neri et al 2013;Smith et al 2014;Unterberger and Holzapfel 2014;Mak et al 2015Mak et al , 2016Gao et al 2015;Nguyen et al 2016;Popov et al 2016;Reddy and Sansom 2016;Chavent et al 2016;Foffano et al 2016;Niesen et al 2017;Tachikawa and Mochizuki 2017). Future investigations will be devoted to simulating dynamical processes involving the cytoskeleton and the membranes, such as the trafficking of macromolecules and vesicles to their sub-cellular localization (Miller et al 2016).…”
Section: Toward Realistic Molecular Simulations Of Cellular Eventsmentioning
confidence: 99%